2003
DOI: 10.1080/16501960310010179
|View full text |Cite
|
Sign up to set email alerts
|

Cortical reorganisation and chronic pain: implications for rehabilitation

Abstract: Recent neuroscientific evidence has revealed that the adult brain is capable of substantial plastic change in such areas as the primary somatosensory cortex that were formerly thought to be modifiable only during early experience. These findings have implications for our understanding of chronic pain. Functional reorganisation in both the somatosensory and the motor system was observed in neuropathic and musculoskeletal pain. In patients with chronic low back pain and fibromyalgia the amount of reorganisationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
1
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(172 citation statements)
references
References 53 publications
6
158
1
7
Order By: Relevance
“…Phantom pain has been related to sensorimotor reorganization in the cerebral cortex contralateral to amputation (Flor, 2003;MacIver et al, 2008), and is believed to originate from unmasking of pre-existing circuits due to removal or inactivation of inhibitory synapses (Ramachandran and RogersRamachandran, 2000), or following changes in callosal connections (Schwenkreis et al, 2003;Giummarra et al, 2007). Cortical reorganization related to nonpainful phantom sensation in amputees, however, has remained controversial (Flor et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Phantom pain has been related to sensorimotor reorganization in the cerebral cortex contralateral to amputation (Flor, 2003;MacIver et al, 2008), and is believed to originate from unmasking of pre-existing circuits due to removal or inactivation of inhibitory synapses (Ramachandran and RogersRamachandran, 2000), or following changes in callosal connections (Schwenkreis et al, 2003;Giummarra et al, 2007). Cortical reorganization related to nonpainful phantom sensation in amputees, however, has remained controversial (Flor et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In amputees, cortical reorganization can be accompanied by phantom limb pain, which is correlated with the degree of overrepresentation [48]. Some forms of chronic pain unrelated to limb loss display a similar manifestation of aberrant cortical plasticity [49,50]. Similar to the implementation of targeted plasticity therapy for tinnitus, pairing VNS with various modalities of cutaneous somatosensory stimulation excluding the overrepresented painful area may potentially reverse associated maladaptive plasticity and reduce the percept of pain.…”
Section: Potential Applications For Other Sensory Disordersmentioning
confidence: 99%
“…50 Recent brain imaging studies (Maihofner et al, 2003;51 Pleger et al, 2005) have shown that those with CRPS 52 have a disrupted cortical map of the affected body part. 53 An association between symptom resolution over time 54 and the corrective reorganisation of cortical limb repre-55 sentation suggests that there is a relationship between 56 the amount of pain and the degree of cortical disorgani-57 sation (Flor, 2003;Maihofner et al, 2004;Pleger et al, 58 2005). The existence of these disturbed representations 59 could serve to influence the pain experience and alter 60 how an individual may perceive their CRPS limb.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%